Nuc‐ErbB3 regulates H3K27me3 levels and HMT activity to establish epigenetic repression during peripheral myelination. Issue 6 (28th March 2016) - Ness, Jennifer K.; Skiles, Amanda A.; Yap, Eng‐Hui; Fajardo, Eduardo J.; Fiser, Andras; Tapinos, Nikos
Abstract : Nuc‐ErbB3 an alternative transcript from the ErbB3 locus binds to a specific DNA motif and associates with Schwann cell chromatin. Here we generated a nuc‐ErbB3 knockin mouse that lacks nuc‐ErbB3 expression in the nucleus without affecting the neuregulin‐ErbB3 receptor signaling. Nuc‐ErbB3 knockin mice exhibit hypermyelination and aberrant myelination at the paranodal region. This phenotype is attributed to de‐repression of myelination associated gene transcription following loss of nuc‐ErbB3 and histone H3K27me3 promoter occupancy. Nuc‐ErbB3 knockin mice exhibit reduced association of H3K27me3 with myelination‐associated gene promoters and increased RNA Pol‐II rate of transcription of these genes. In addition, nuc‐ErbB3 directly regulates levels of H3K27me3 in Schwann cells. Nuc‐ErbB3 knockin mice exhibit significant decrease of histone H3K27me3 methyltransferase (HMT) activity and reduced levels of H3K27me3. Collectively, nuc‐ErbB3 is a master transcriptional repressor, which regulates HMT activity to establish a repressive chromatin landscape on promoters of genes during peripheral myelination. GLIA 2016;64:977–992 Main Points: Nuc‐ErbB3 knock‐in mice exhibit peripheral hypermyelination. Nuc‐ErbB3 regulates total levels of H3K27me3 and HMT activity. Nuc‐ErbB3 induces transcriptional repression of myelination associated genes.